A dimensão subjetiva da experiência intercultural de estudantes africanos no Brasil - Rodrigues, Carla Saturnina Barreto (2021)
Academic mobility is a phenomenon that has gained adherence and space for discussion. It is a theme that there are probable, political, social, cultural, and educational behind it. The proposal that we bring in this research is to investigate African students' reports on the phenomenon of academic mobility. We seek to understand, through the category of socio-historical psychology, the dimension of specification, how the subjective senses and meanings in this phenomenon are put or formed as occurrences. To this end, it researches the Google platform questionnaire to reach a larger number of African students in several cities in Brazil. These are in the range of twenty-nine years, all of them doing higher education in Public Universities in Brazil. We made a very short e of graphics to facilitate the subjects' responses, and then we continued with the qualitative descriptions. Based on this material, we carry out an analysis and conclude with the aspects essential for training and understanding and the subjective dimension of academic mobility